Listeners’ Reactions to Four French Accents: a Study of Gender as a Variable in Linguistic Attitudes - Brown, Catherine; Cichocki, Wladyslaw (Linguistica Atlantica, 1995)
This study examines two aspects of the role of gender in linguistic attitudes. First, it studies the issue of the dimensions which underlie linguistic attitudes, in particular whether features of masculinity and femininity play a role in speech evaluation. Second, it looks at differences among individual listeners from the point of view of how female and male listeners are similar and different in their evaluations. The study is based on a survey in which a group of university students evaluated four French accents found in schools in the province of New Brunswick, Canada: Acadian French, European French, Quebec French, and French spoken by an anglophone, which we will refer to as anglophone French.